Development of Muslim Women Entrepreneurship: Islamic Perspective and Transformation of Social Roles - Haruni Ode; Reni Rosari; Rika Fatimah; Heru Kurnianto Tjahjono (Journal of Islamic Economic and Business Research, 2025)
This study develops a conceptual understanding of Muslim women's entrepreneurship by emphasizing how Islamic values ​​shape their motivations, decision-making processes, and social roles in business activities. Despite the continued growth of research on women's entrepreneurship, a theoretical gap remains regarding how Islamic religiosity, sharia norms, and religious social constructions simultaneously integrate to shape Muslim women's entrepreneurship models. Existing literature tends to highlight socio-cultural aspects or gender barriers separately, without providing an integrated conceptual framework that explains the interplay between Islamic values, religious identity, and the structural dynamics faced by Muslim women. This study offers a theoretical contribution by proposing a values-based perspective on Muslim women's entrepreneurship that integrates Islamic business ethics, principles of justice, and the demands of domestic and social roles. The findings demonstrate that Muslim women's entrepreneurship is not simply an economic response, but a practice negotiated religiously, culturally, and structurally. Thus, this article provides a conceptual foundation for understanding Muslim women's entrepreneurship as a phenomenon that cannot be explained solely through conventional entrepreneurship theories, but requires an approach rooted in Islamic values ​​and epistemology.